Atypical Myocardial Infarction with Apical Thrombus and Systemic Embolism: A Rare Presentation of Likely JAK2 V617F-Positive Myeloproliferative Neoplasm. (19th May 2020) - Atere, Muhammed; Al-Zakhari, Rana; Collins, Jennifer; Rotatori, Francesco; Muzangwa, Lloyd
Abstract : A few types of myeloproliferative neoplasms may be significant for Janus-associated kinase 2 mutation, JAK2 V617F, including polycythemia vera, essential thrombocythemia, and primary myelofibrosis. The prevalence of JAK2 mutation is low in the general population but higher in patients with myeloproliferative neoplasms. Some patients with JAK2 V617F-positive essential thrombocythemia are asymptomatic, but others may develop hemorrhagic or thromboembolic complications. Thromboembolism may occur in vessels of high flow organs like the heart and, thereby, present as myocardial infarction. Nonetheless, these patients are usually symptomatic with complaints of chest pain, for example. Atypical (asymptomatic) myocardial infarction with mild thrombocytosis may be the first clue for possible essential thrombocythemia with JAK2 V617F. In this report, we discuss a case of atypical (asymptomatic) myocardial infarction with secondary thromboembolism in a patient positive for JAK2 V617F with a likely myeloproliferative neoplasm.